A Single-Event MicroKinetic model for the cobalt catalyzed Fischer-Tropsch Synthesis - Van Belleghem, Jonas; Ledesma, Cristian; Yang, Jia; Toch, Kenneth; Chen, De; Thybaut, Joris W.; Marin, Guy B. (Applied catalysis. A, General, 2016)
[Display omitted] •Validation of Single-Event MicroKinetic methodology for the Co catalyzed Fischer-Tropsch Synthesis.•The adjustable parameters are all statistically significant and physicochemical meaningful.•Deviations from Anderson-Schulz-Flory distribution are explained by symmetry and adsorption effects.•Activity difference between Fe and Co catalysts is interpreted in terms of the oxygen atomic chemisorption enthalpy. The Single-Event MicroKinetic methodology has been successfully extended from Fe to Co catalyzed Fischer-Tropsch Synthesis. A total of 82 experiments were performed in a plug flow reactor with a H2 to CO molar inlet ratio between 3 and 10, a temperature range from 483 to 503K, CO inlet partial pressures from 3.7 to 16.7kPa and space time varying between 7.2 and 36.3(kgcats)mol−1. Via regression, statistically significant and physicochemically meaningful estimates were obtained for the activation energies in the model and the H, C and O atomic chemisorption enthalpies as required for the UBI-QEP method. A reaction path analysis allowed relating the observed deviations from the Anderson-Schulz-Flory distribution, i.e., a high methane and low ethene selectivity, to the symmetry numbers and a higher chemisorption enthalpy of the metal methyl species compared to the other metal alkyl species. Simulations at industrially relevant conditions show that, as a catalyst descriptor, the H atomic chemisorption enthalpy crucially determines both the CO conversion and the C5+ selectivity. The higher FTS activity of Co compared to Fe is explained via the higher oxygen atomic chemisorption enthalpy on the latter compared to the former.